Hubungan antara Kepuasan Pasien dan Kualitas Hidup pada Pasien Hemodialisis - Reisha Anom Dwijokangko; Wantonoro Wantonoro; Diyah Candra (Journal of Health, Medical, and Psychological Studies, 2026)
Chronic Kidney Disease patients undergoing hemodialysis experience various physical, psychological, and social challenges that may affect their quality of life. Patient satisfaction with health services is considered an important factor that may influence treatment outcomes and well-being. This study aimed to determine the relationship between patient satisfaction and quality of life in hemodialysis patients. This study used a quantitative descriptive correlational design with a cross-sectional approach. The population consisted of 163 hemodialysis patients at RS PKU Muhammadiyah Gamping, with a sample of 127 respondents selected using purposive sampling based on the Slovin formula. Data were collected using a patient satisfaction questionnaire and the Kidney Disease Quality of Life–Short Form 36 (KDQOL-SF 36). Data were analyzed using Spearman’s rho correlation test with a significance level of p < 0.05. The results showed that all respondents reported being satisfied (100%). In conclusion, although satisfaction was high, no significant relationship was found with quality of life.